STRATEGY DEVELOPMENT OF ECOTOURISM IN NATURAL RESERVATION AREA ARFAK IN MOKWAM VILLAGE AND SURROUNDING - Alfa Ahoren (Journal of Business on Hospitality and Tourism, 2017)
Ecotourism as a form of responsible tour to natural areas conducted with the aim to conserve the environment also preserve the life and the welfare of the local population. This research was conducted in the conservation area of the mountains of Arfak inside at Mokwam, Kwaw and Syou village, Warmare district, Manokwari Regency, has the purposes to know the ecotourism potential, Mokwam society’s attitude towards the ecotourism development and its strategy in conservation areas in Arfak mountains at Mokwam village and its surrounding. The advantage is to expand the development of ecotourism atCAPAarea, can be used as consideration in ecotourism development and also as an alternative to protect the environment and the culture of local population towards the exploitation in order to remain sustainable. The research method use qualitative methods. This method was used to get the data or qualitative description aboutCAPAarea. The data analysis technique use descriptive-qualitative and the analysis of SWOT. The results of this research are potential tourism attractions, accommodations, facilities, accessibility and additional services. The attitude of the local people inCAPAarea now is in the phase of euphoria which is they are supporting the development of ecotourism. The strategies that can be done through the programs such as: product development planning of ecotourism, structuring the organization and the management ofCAPAarea, do marketing of ecotourism product.